Analisis Beban Kerja Dengan Metode Workload Analysis (WLA) Dalam Menentukan Jumlah Tenaga Kerja Optimal Di PT INDOJT - Hermanto Hermanto; Widiyarini Widiyarini (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2020)
Human resources is one of the important elements in the implementation of a project because of its considerable influence on costs and time. The workload borne by the workforce is closely related to the efficiency and effectiveness of a project. There are many ways that can be done in the efficiency of human resources, among others, by optimizing the number of workers. PT Jaya Teknik Indonesia, as one of the companies engaged in the contractor of Mechanics, Electrical, Electronics and Information Technology. also can not be separated from the problem of this workload, work that doubles with other jobs is one of the causes. By using the Workload Analysis (WLA) method to determine workload. From the results of the WLA analysis, it was found that the Quality control Tower 1 workload was 119%, Supervisor Tower 2 was 135% and Supervisor Tower 3 was 124% besides that, after calculation the optimal number of employees was obtained by adding 1 labor in Tower 1, Tower 2 and Tower 3.